Assessing the Power of Electron Back Scattering Diffraction Characterization of Deformed F-138 Steel from the View Point of Crystal Diffraction - Bolmaro, Raul Eduardo (2014)
Microstructural characterization by combined EBSD and X-ray diffraction analysis is shown for an FCC material deformed by rolling and further heat treatment on air. The wide variety of x-rays sources combined with EBSD allows some correlations between microstructural parameters to be withdrawn by carefully analyzing x-ray peak broadening. The combination of both techniques provides a deeper understanding of anisotropic accumulation of dislocation arrays on a deformed F 138 stainless steel. The anisotropy results in a smaller peak breadth for crystal orientations with [110] planes contained on the rolling plane, further explained as resulting from a lower storage of dislocations. After heat treatment the effect is reverted and the formerly less misoriented orientations become more uniformly oriented revealing a faster dislocation migration and annihilation and/or trapping